Duality in the analysis of responses to nonlinear systems - Dong Anh, Nguyen (Vietnam Journal of Mechanics, 2010)
The paper provides a new view on the averaging procedure and equivalent linearization in the study of nonlinear mechanics. It is shown that the duality of those techniques can be used to obtain better approximate solutions or to separate the original nonlinear systems subjected to periodic and random excitations into deterministic and stochastic ones.